Measles antibodies in cord blood in Portugal: Possible consequences for the recommended age of vaccination - Gonçalves, Guilherme (2017)
The optimum age to give the first dose of measles vaccine must balance the risks of disease and vaccine failure. Both are influenced by the levels of transplacentally acquired maternal antibodies. This study was conducted in the Obstetric service of Portuguese hospital, in 2012-2013. Mothers were recruited after informed consent. Measles IgG was measured in 206 cord sera, using a commercial immunoassay. Geometric mean concentrations (and 95% CI) were 1849mIU/ml (1196-2857) and 790mIU/ml (618-1008) in cord sera of newborns from unvaccinated and vaccinated mothers respectively. Maternal age and vaccination status were both associated with the concentration in cord sera, but maternal age was the major predictor. The likely explanation is the same already mentioned in other studies: as a vaccination program progresses, vaccination coverage increases as measles incidence decreases. That results newborns from younger vaccinated mothers having less measles antibodies while the older mothers are more likely to have been infected with the wild virus. As the proportion of vaccinated mothers increase, developed countries tend to anticipate the recommended age of the first dose to 12 months of age. Models using hypothetical measles antibody decay rates in infancy were explored. Anticipating the first dose of MMR1 in Portugal to the age of 12 months might have not been the best decision but results were not conclusive, and arguments supporting or not the anticipation were discussed.